2009
DOI: 10.1080/01446190802596220
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the bid/no bid decision in the Saudi Arabian construction contractors

Abstract: The bid/no bid decision requires an understanding of a company's assessment in relation to factors affecting the decision. Different companies might have different assessment values. The aim is to investigate how bid/no bid decisions are influenced by different characteristics of contractors. Various factors are identified and then analysed in order to investigate their influence and relative significance. A questionnaire survey was used to identify and rank the factors affecting the bidding decision and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 10 publications
8
73
0
Order By: Relevance
“…They found that the importance of different factors varies greatly according to the contractor size. In a similar study developed in Saudi Arabia, Bageis and Fortune (2009) indicated that the most critical factors are the size and characteristics of the contractor and the type of owner. Enshassi et al (2010) discovered that financial capability (of contractor and owner), project value, resources availability and stability of the construction industry were the key factors in Palestine.…”
Section: Variables Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the importance of different factors varies greatly according to the contractor size. In a similar study developed in Saudi Arabia, Bageis and Fortune (2009) indicated that the most critical factors are the size and characteristics of the contractor and the type of owner. Enshassi et al (2010) discovered that financial capability (of contractor and owner), project value, resources availability and stability of the construction industry were the key factors in Palestine.…”
Section: Variables Identificationmentioning
confidence: 99%
“…Not bidding for a project that could be won results in losing an opportunity to make profit, improve market position, and strengthen relationships with other stakeholders . On the other hand, bidding for a project that is not likely to be won results in loss of time, money and effort, important resources that could have been used for a better option (Bageis, Fortune 2009). Moreover, continually losing bids could result in a bad reputation (Lin, Chen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Early work mainly involved the bidding factors unique to countries and geographical regions, such as Ahmad and Minkarah [24] identified 31 key factors affecting the bidding decision process of contractors in the USA, which provided the foundation for follow-up studies [7]. Shash [25] identified 55 factors characterizing the bidding decision-making of contractors in the UK.…”
Section: Project Factors For Bidding Decisionsmentioning
confidence: 99%
“…Bidding decisions and factors influencing the processes involved have elicited wide attention in previous studies relating to construction management (CM) [6][7][8][9][10]. However, the focus of these studies is mainly on project characteristics, the construction companies' resources available, and economic environmental factors such as market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating and tendering handbooks provide guidelines on selection criteria based on the experience of their authors (among others, Brook, 2011, p. 96;Cartlidge, 2013, p. 3;Stevens, 2012, p. 93). Enquiries on factors affecting the bid/no bid decision were conducted in many countries: in Great Britain (Shash, 1993), Egypt (Hassanein, 1996), the United States (Ahmad & Minkarah, 1998), Syria (Wanous et al, 2000), Singapore (Chua & Li, 2000), Saudi Arabia (Bageis & Fortune, 2009), Poland (Leśniak & Plebankiewicz, 2015), Australia (Shokri-Ghasabeh &Chileshe, 2016), andNigeria (Oyeyipo et al, 2016). As the authors drew from each other, the lists of initial criteria were rather consistent regardless of the country of origin.…”
Section: Decision To Bidmentioning
confidence: 99%